Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content:1. Experience of teaching computer courses using Madrasati platform during coronavirus pandemic from the teachers’ perspectiveCo-Prof. Amal Abdullah Al Ibrahim2. The reality of using digital stories among students with autism in the early intervention stage from the point of view of female teachers in JeddahMrs. Hala Harban Almutiri3. Learning and Study Strategies according to the Weinstein and Palmer LASSI ModelMr. Mohammed Abdallah Almazruii4. The Effect of Using Verbal Mathematical Problem Solving on Developing Reading Comprehension among First Grade Middle School StudentsMr. Abdulaziz Saeed Yahya Almaadi, Dr. Mousa Abdulmouin Mohammed Alqarni5. The effect of using the cognitive trips strategy through The Web Quest toward tenth-grade students Motivation in social studies in the Sultanate of OmanDr. Khalid Nasser Abdullah Al-Toubi, Prof. Mohammed Y. M. Mai8. The Values Contained in the Developed Books of Islamic Education at the Upper Three Grades in Primary Stage in Saudi ArabiaDr. Fahad Oudah Alatawi7. The effect of the cognitive apprenticeship strategy on the achievement and memorization of literature and texts among the fifth literary studentsDr. Natiq Saeed Ghayyib
Keywords: Journal of Curriculum and Teaching Methodology